Daily behaviors of long-tailed macaque (Macaca fascicularis) in the semi-natural enclosure on Tinjil Island, Banten, Indonesia - Syafutra, Randi (BIO PALEMBANICA, 2024)
The research investigates the daily behaviors of long-tailed macaques (Macaca fascicularis) within a semi-natural enclosure on Tinjil Island, Banten, Indonesia, aiming to enhance understanding of their adaptability and social dynamics. Data were collected through scan sampling over five days, focusing on 20 individuals of varying age and sex. The results highlight locomotion, feeding, and resting as dominant activities, with feeding strategies adapting to food availability and environmental conditions. Social behaviors, including grooming and play, were critical for group cohesion, hygiene, and development. Supplementary feeding reduced competition for resources, stabilizing social interactions within the group. Agonistic and vocalization behaviors further underscored the species' complex social structure. These findings offer valuable insights for improving conservation management, enhancing the welfare of captive populations, and addressing the species’ endangered status. This research contributes to a foundational understanding of M. fascicularis behavior, guiding future conservation and management efforts for this ecologically and scientifically significant primate.